Effect of the inlet angle on the performance of a cyclone separator using CFD-DEM - Wang, Shuyan; Li, Haolong; Wang, Ruichen; Wang, Xu; Tian, Ruichao; Sun, Qiji (Advanced powder technology : the international journal of the Society of Powder Technology, Japan, 2019)
[Display omitted] •Hydrodynamic characteristics of cyclones are simulated using CFD-DEM.•The impact of inlet angle on flow behavior is studied.•Reynolds stress turbulence model is used to capture gas turbulence.•The effect of particle size on the performance of a cyclone separator is analyzed. Hydrodynamic characteristics in a cyclone separator are simulated by means of DEM-CFD. Reynolds stress turbulence model (RSM) is used to capture gas turbulence. By changing the inlet angle, the distributions of pressure drop, tangential and axial velocity of gas phase are obtained within the cyclone. Simulated results indicate that the flow pattern consists of two regions: loss-free vortex region and forced vortex region. The negative inlet angle brings about a larger pressure drop comparing to positive inlet angle. The separation efficiency and trajectory of particles from simulation are obtained. The effects of inlet angle and particle size on separation efficiency are quantified. The separation efficiency is increased with an increase of particle size, while the separation efficiency firstly increases and then declined as inlet angle changes from negative to positive. An agreement between the numerical simulation and experimental results has been achieved in a cyclone separator.